2018
DOI: 10.1016/j.stem.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Organoids from Human Pluripotent Stem Cells Delineate Sox2 Functions during Esophageal Specification

Abstract: SUMMARY Tracheal and esophageal disorders are prevalent in humans and are difficult to accurately model in mice. We therefore established a three-dimensional organoid model of esophageal development through directed differentiation of human pluripotent stem cells. Sequential manipulation of BMP, WNT, and RA signaling pathways was required to pattern definitive endoderm into foregut, anterior foregut (AFG), and dorsal AFG spheroids. Dorsal AFG spheroids grown in a 3D matrix formed human esophageal organoids (HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 66 publications
(107 reference statements)
4
110
0
3
Order By: Relevance
“…The underlying mechanisms through which epithelial regional identity determines the characters of the surrounding mesenchyme remain to be elucidated. In a previous study, SOX2-deficient AFG failed to express some Wnt antagonists (Trisno et al, 2018), whereas in other studies, the anteroposterior organization of the gut tube depended on retinoic acid signaling (Bayha et al, 2009;Wang et al, 2006). Hence, the regulation of these signals by epithelial tissues may contribute to the coordinated development of epithelial and mesenchymal components of the AFG.…”
Section: Surrounding Mesenchymal Tissues Developed Concordant With Thmentioning
confidence: 84%
See 1 more Smart Citation
“…The underlying mechanisms through which epithelial regional identity determines the characters of the surrounding mesenchyme remain to be elucidated. In a previous study, SOX2-deficient AFG failed to express some Wnt antagonists (Trisno et al, 2018), whereas in other studies, the anteroposterior organization of the gut tube depended on retinoic acid signaling (Bayha et al, 2009;Wang et al, 2006). Hence, the regulation of these signals by epithelial tissues may contribute to the coordinated development of epithelial and mesenchymal components of the AFG.…”
Section: Surrounding Mesenchymal Tissues Developed Concordant With Thmentioning
confidence: 84%
“…Under this condition, single AFG epithelial tubes connecting the pharynx and stomach developed, comprising columnar epithelial cells and expressing NKX2.1, indicating a gain of tracheal/bronchial characteristics and loss of esophageal characteristics (Figs 1 and 4). Trisno et al (2018) similarly ablated Sox2 in the endoderm and reported the development of NKX2.1-expressing AFG epithelia that lacked esophagus-characteristic p63 expression.…”
Section: Surrounding Mesenchymal Tissues Developed Concordant With Thmentioning
confidence: 93%
“…Mouse mutations in these patterning genes can result in TEDs similar to those seen in patients. For example, Sox2 and Nkx2-1 knockouts result in EA and TA, respectively (Minoo et al, 1999;Que et al, 2007;Trisno et al, 2018), while HH pathway mutations, such as in the ligand Shh or the transcription factors Gli2 and Gli3, can cause a spectrum of defects ranging from EA/TEF to laryngotracheoesophageal clefts (LTECs) (Litingtung et al, 1998;Motoyama et al, 1998;Rankin et al, 2016;Tabler et al, 2017). How these mutations result in TEDs is unclear since the cellular processes that HH regulates in this context are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, reports of complex organotypic structures had previously been reported for pancreatic buds (Micallef et al 2007) and intestine (Spence et al 2011). Application of this type of approach was rapidly adopted to spectacular effect, with the formation of tissue as complex as the human cerebral cortex (Lancaster et al 2013) and specific tailoring of differentiation protocols to generate the entire extent of the gastrointestinal tract from oesophagus to colon (McCracken et al 2014(McCracken et al , 2017Múnera et al 2017;Trisno et al 2018). What is evident from all of these protocols is that the tissue generated is fetal in nature and that morphogenetic patterning is variable between organoids and even further between lines and individual experiments (Phipson et al 2019).…”
Section: Building a Kidney Organoid From Pluripotent Stem Cellsmentioning
confidence: 99%